Intervensi untuk Mengurangi Academic Anxiety pada Mahasiswa Rumpun Kesehatan: Scoping Review - Hernanda, Messayu Fathasari (Universitas Malahayati, 2023)
ABSTRACT Academic and emotional demands on healthcare students can cause mental health problems, one of which is academic anxiety. Academic anxiety is one type of anxiety that comes from the ongoing educational process. Academic anxiety experienced by health students can affect their academic achievement. Thus, various interventions are needed to overcome the impact of academic anxiety. This study aimed to map out the interventions used to reduce academic anxiety. This research method is a scoping review with PRISMA-ScR guidelines. The literature search was conducted using the PubMed, CINAHL & Springerlink databases, and the Google Scolar&ProQuest search engine. The year range of the article is the last 10 years. The keywords used were